SCIENTIFIC BASIS AND APPLICATION FUNCTIONS OF ORGANIZATIONAL PSYCHOLOGY CONSULTING - Harutyunyan Н. А. (Modern Psychology, 2019)
The article is dedicated to the organizational consultancy issues and activities. The organisational and psychological consultation aspects are analysed and clarified in theoretical framework. The role of psychological consultancy is discussed, in the scope of operating organizations’ effectiveness enhancement in nowadays market relations.